Considerações sobre a sintaxe do português do Brasil em gramáticas do período científico (1880-1920): uma abordagem historiográfica - Marinho, José Eric da Paixão (2020)
The discussion about the existence of a Portuguese language from Brazil is not recent. With regard to Brazilian grammar, Cavaliere (2014) and Coelho et al. (2014) point to the appearance of the first syntactic data of Brazilian Portuguese in grammars produced in the so-called “scientific” period, between 1880 and 1920. Grammars of this period, such as Júlio Ribeiro (1881), João Ribeiro (1887), Pacheco & Lameira (1887) and Carneiro Ribeiro (1890), motivated by political, social and linguistic factors, already pointed to the existence of the particularities of the language of Brazilians in their works. After performing a mapping of grammars produced in the nineteenth century, and verifying through a pre-analytic process that, in fact, the first significant appearances of syntactic data from Brazilian Portuguese occur in grammars produced from 1881,we aim in this dissertation to investigate the treatment given to the syntactic specificities of Brazilian Portuguese in grammars of the scientific period (1880 to 1920). We took as research object for this study the following grammars: Ribeiro (1881), Pacheco & Lameira (1887), Ribeiro (1887; 1887 [1889]), Alves (1897), Pereira (1907), Gomes (1913 [1887]), Maciel (1914 [1890]), e Carneiro Ribeiro (1915 [1890]). To achieve this goal, the theoretical-methodological framework of the Historiography of Linguistics will be used, based on the studies of Koerner (1996; 2014; 2016), Swiggers (2010; 2013), Altman (2004) and Batista (2013), along with the secondary sources (VIEIRA, 2018; BORGES NETO, 2018; POLACHINI, 2018; among others), in the reconstruction and discussion of the opinion climate of the time and its possible influences on the treatment given to the syntactical specificities of Brazilian Portuguese in grammars selected for parsing. The results show that, despite a growing rhetoric in favor of language evolutionary processes and a greater appearance of the specificities of Brazilian Portuguese in the selected sources, the syntactic treatment given to such specificities is mostly prohibitive and from a perspective of inferiority to the prescribed and idealized Lusitanian norm.